The effect of Pumpkin peels (Cucurbita maxima) on the quality of Japanese quail flesh - Munirah Azman,; Fauziah Tufail Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The use and benefit of Pumpkin (Cucurbita maxima) peel is still not prominent and acknowledged by many people till now. The peel which is reported to be abundant with beta-carotene are not palatable and commonly discarded. The main objective of this experiment is to determine the effect of different concentrations of pumpkin peel powder (PPP) as feed formulation on the flesh quality of Japanese quail (Coturnix japonica). The following treatments were applied; commercial feed with 0% PPP (Treatment 1; T1), 2% (Treatment 2; T2); 4% (Treatment 3; T3) and 6% (Treatment 4; T4) for 3 weeks after fully fed with commercial feed for 2 weeks. The main analytical tests conducted were feed analysis, carotenoid content, drip loss, colour and texture. Carotenoid content was analysed by using spectrophotometer. The results obtain indicated that the highest concentration (6%) of pumpkin peel powder showed the highest reading of carotenoid content (p<0.05) while treatment 2 with 2% of PPP obtain the highest weight gain (p<0.05). In conclusion, this study showed that quail feed which supplemented with higher PPP may help in producing quail flesh with antioxidant properties.